Hydraulic Characterization of Locally Manufactured Drip Emitters - Mangrio, Abdul Ghafoor; Dahri, Zakir Hussain; Ikram, M. z.; Ahmed, Bashir (Biological Sciences - PJSIR, 2007)
Trickl e i rr i gat ion system s were design ed and managed to deliver frequent light water application s to wet on l y a port ion of th e soi l su rface. In i ti a ll y, selection of an emitter depends on th e soi l to be wetted, plant water req ui rement, emitter discharge and th e topography of the soi l. The pressu re-d i scharge relationshi ps and man ufacturers’ coefficient of vari ation of five di fferent loca ll y man ufactur ed dr i p emitters were determined . The em itters were tested wi th different pl acements. They were operated at pressure ranging from 3.50-21 .00 m eter head (5-30 ps i) wi th i n crements of 5 psi. All th e measurements were repl i cated th ri ce for th e five types of em i tte rs. The coefficient of variation ( Jis an average for all types of micro -tu be and nursery emitters , marginal for tu rbo and m i cro-j et and un acceptabl e for spi ra l em i tters. On t h e basi s of water appl i ca ti on u n iformity coefficient (U s %), turbo, micro-j et, n u r sery an d m i cro-tu be emi tt ers fal l i n t h e acceptabl e ran ge. The em i tters were developed and evaluated i n coll aboration w i t h th e l ocal i nd u try.